A comparative clinical study of two different attachment systems and implant stability in implant-supported mandibular overdentures - Ammar Omar Belal; Moataz Mostafa Bahgat Elmahdy; Sayed Mohammed Mohammed El Masry; Mohamed Ezzat Elsayed (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Implant stability is crucial for the long-term durability of implant-supported removable dentures. Understanding the clinical impact of attachment systems such as Novaloc and Locator on stability is essential for their potential prognosis. Purpose: The aim of this study is to compare the effects of Novaloc and Locator attachment systems on implant stability in implant-supported overdentures. Methods: The research sample consisted of 10 patients, all entirely edentulous in the lower and upper jaws. Each patient received a conventional complete denture in addition to two implants in the mandible. Equal numbers of patients were assigned to Group 1: Novaloc attachment system and Group 2: attachment system for locators. Implant stability was evaluated using the MegaGen implant stability quotient device and repeated after 4, 8, and 12 months. The SPSS program was used to collect, calculate, and statistically analyze the data. Results: According to one-way ANOVAs and independent t-tests conducted throughout the observation period, both groups demonstrated an improvement in implant stability, but the Novaloc group showed superiority, with statistically significant differences (P > 0.05). Conclusion: Based on the study’s findings, in comparison to the Locator system, the Novaloc attachment system offers better implant stability during a 1-year monitoring period.